A Preliminary Application of Social Cognitive Theory to Nonsuicidal Self-Injury - Hasking, Penelope; Rose, A. (Springer New York LLC, 2016)
Researchers have established a relationship between exposure to nonsuicidal self-injury (NSSI), and increased probability of engaging in the behavior, but few have endeavored to explain the mechanisms underlying the relationship. We drew on Social Cognitive Theory to argue that core cognitions, including NSSI outcome expectancies and self-efficacy expectancies, moderate this relationship. We also explored whether knowledge about NSSI and attitudes toward the behavior played a role in this relationship. A sample of 389 university students (73.1 % female, M age = 20.90, SD = 2.36), completed online questionnaires assessing the constructs of interest. Our findings support the application of Social Cognitive Theory to better understanding NSSI, with clear links between expectancies, self-efficacy and NSSI. Further, these cognitions moderated a number of exposure-NSSI relationships. Implications of these findings for theory, research and intervention are discussed.